Integrating Clinical Signs at Presentation and Clinician's Non-analytical Reasoning in Prediction Models for Serious Bacterial Infection in Febrile Children Presenting to Emergency Department - Urbane, Urzula Nora; Petrosina, Eva; Zavadska, Dace; Pavare, Jana (Frontiers in Pediatrics, 2022)
Objective: Development and validation of clinical prediction model (CPM) for serious bacterial infections (SBI) in children presenting to emergency department (ED) with febrile illness, based on clinical variables, clinician’s “gut feeling”, and “sense of reassurance”. Materials and methods: Febrile children presenting to the ED of Children’s Clinical University Hospital (CCUH) between 1st of April 2017 and 31st of December 2018 were enrolled in a prospective observational study. Data on clinical signs and symptoms at presentation, together with clinician’s “gut feeling” of something wrong and “sense of reassurance” were collected as candidate variables for CPM. Variable selection for the CPM was performed using stepwise logistic regression (forward, backward, and bidirectional), Akaike information criterion was used to limit the number of parameters and simplify the model. Bootstrapping was applied for internal validation. For external validation, the model was tested in a separate dataset of patients presenting to six regional hospitals between 1st of January and 31st of March 2019. Results: The derivation cohort consisted of 517, 54% (n=279) were boys, the median age was 58 months. SBI was diagnosed in 26.7% (n=138). Validation cohort included 188 patients, the median age was 28 months, 26.6% (n=50) developed SBI. Two CPMs were created, CPM1 consisting of sixeight clinical variables, and CPM2 with four clinical variables plus “gut feeling” and “sense of reassurance”. The area under curve (AUC) for Receiver operating characteristics (ROC) curve of CPM1 was 0.744 (95% CI 0.683-0.805)0.738 (95% CI 0.688-0.788) in derivation cohort and 0.692 (95% CI 0.604-0.780) 0.677 (0.586-0.767) in validation cohort. AUC for CPM2 was 0.783 (0.727-0.839) and 0.752 (0.674-0.830) in derivation and validation cohorts, respectively. AUC of CPM2 in validation population was significantly higher than that of CPM1 (p=0.037, 95%CI (-0.129; -0.004). A clinical evaluation score was derived from CPM2 to stratify patients in “low-risk”, “grey area”, and “high-risk” for SBI. Conclusion: Both CPMs had moderate ability to predict SBI and acceptable performance in validation cohort. Adding variables “gut feeling” and “sense of reassurance” in CPM2 improved its ability to predict SBI. More validation studies are needed for assessment of applicability to all febrile patients presenting to ED.